Pengaruh Asistensi Relawan Pajak, E-Filling, Dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi dalam Pelaporan SPT Tahunan di Kantor Pelayanan Pajak (KPP) Pratama Gianyar - Ruhni, Zaedar; Meitriana, Made Ary (Universitas Pendidikan Ganesha, 2023)
This study aims to examine the effect of volunteer tax assistance, e-filing, and tax socialization on the compliance of individual taxpayers (WPOP) in reporting annual tax returns (SPT) at the Pratama Gianyar Tax Office (KPP). This type of research is causal research with a quantitative approach. The population in this study was all individual taxpayers registered at KPP Pratama Gianyar, totaling 288.229 taxpayers. The number of samples in this study was 100, calculated based on the Slovin formula and taken using a proportional random sampling technique. The data used in this study are primary and secondary. The data analysis technique used is multiple linear regression analysis. Based on the results of multiple linear regression, the regression equation Y = 60,463 – 0,384+ 0,332 – 0,334 is obtained. The results of this hypothesis test indicate that the e-filling variable has a positive and significant effect on individual taxpayer compliance at the Gianyar Pratama Tax Service Office, while the variables volunteer tax assistance and tax socialization have a negative and significant effect on individual taxpayer compliance at the Gianyar Primary Tax Service Office. Subsequent results show that volunteer tax assistance, e-filling, and tax socialization together have an effect on individual taxpayers (WPOP) in reporting annual SPT at KPP Pratama Gianyar, with a significance value of 0.000 < 0.05 and Fcount > Ftable (7.371 > 3.091).